Integrating Reciprocal Teaching and Edmodo to Improve the Students' Reading Comprehension for Eleventh Graders - Marko Wibisono; Francisca Maria Ivone; Enny Irawati (Universitas Negeri Malang, 2019)
Abstract: The purpose of this collaborative classroom action research was to improve the students' reading comprehension in analytical exposition text. The subjects of this study were 23 high school students. The instruments in data collection were reading test, observation checklist, and field notes. The finding of the research signify that the implementation of Reciprocal teaching and Edmodo integration could improve the students' reading achievement and involvement. The students could enhance their average reading score, which was higher than the minimum passing score. Also, all the students increased their reading score at least 10 points higher than their initial test result. Overall, 19 students passed the minimum passing score. The students' involvement in the RTT classroom implementation also affirmed an increase in the last meeting other than the first meeting. Key Words: reciprocal teaching strategy, reading, comprehension Edmodo Abstrak: Tujuan penelitian tindakan kelas kolaboratif ini adalah untuk meningkatkan kemampuan membaca siswa dalammemahamitekseksposisianalitis. Subjekdalam penelitian ini adalah 23 siswa SMA. Instrumen yang digunakan untuk pengumpulan data adalah tes pemahaman bacaan, lembar pengamatan, dan catatan lapangan. Hasil penelitian adalah penerapan integrasi Reciprocal Teaching Technique (RTT) dan Edmodo berhasil meningkatkan kemampuan siswa dalam memahami bacaan dan keterlibatan siswa dalam kegiatan pembelajaran. Terdapat peningkatan nilai rata-rata yang lebih tinggi dari nilai ke-tuntasan belajar minimal. Nilai masing-masing siswa meningkat 10 poin dibandingkan dengan tes sebe-lumnya. Secara keseluruhan, nilai 19 siswa melampaui nilai ketuntasan belajar minimal. Keterlibatan sis-wa dalam penerapan RTT di dalam kelas juga menunjukkan peningkatan pada pertemuan terakhir daripada pertemuan pertama. Kata kunci: strategi mengajar timbal balik, membaca, pemahaman Edmodo